The EYA-SO/SIX complex in development and disease - Xu, Pin-Xian (Pediatric nephrology (Berlin, West), 2013)
Eyes absent (EYA) and Sine oculis (SO/SIX) proteins function as transcriptional activation complexes and play essential roles in organogenesis during embryonic development in regulating cell proliferation and survival and coordination of particular differentiation programs. Mutations of the Eya and So/Six genes cause profound developmental defects in organisms as diverse as flies, frogs, fish, mice, and humans. EYA proteins also possess an intrinsic phosphatase activity, which is essential for normal development. Here, we review crucial roles of EYA and SO/SIX in development and disease in mice and humans.